Synthesis of Au, Ag, Curcumin Au/Ag, and Au-Ag Nanoparticles and Their Nonlinear Refractive Index Properties. (29th September 2016) - Abdulwahab, F.; Henari, F. Z.; Cassidy, S.; Winser, K.
Abstract : Nanoparticles of gold and silver were prepared by a reduction method and by employing green chemistry principles such as using curcumin as a reducing and a stabilizing agent. The formation of nanoparticles was confirmed by UV-Vis absorption spectra and TEM. Mie theory was used to determine the particle sizes. The nonlinear refraction and absorption properties of the particles were measured using the z-scan technique. A large value of third-order nonlinearities was obtained using the nanoparticles produced.